Transparent non-stoichiometric Tb2.45Hf2O7.68 magneto-optical ceramics with high Verdet constant. (November 2021) - Zhang, Lixuan; Li, Xiaoying; Hu, Dianjun; Xie, Tengfei; Wu, Lexiang; Yang, Zhaoxiang; Li, Jiang
Abstract: Transparent Tb2.45 Hf2 O7.68 ceramics were fabricated successfully by reactive sintering at 1700 °C for 3 h with hot isostatic pressing (HIP) post-treatment at 1700 °C for 3 h. In-line transmittance of the Tb2.45 Hf2 O7.68 ceramic specimen with the thickness of 2.0 mm reached 79.4% at 1064 nm. X-ray diffraction was used to verify the existence of pyrochlore phase and the occupation sites of Tb 3+ were discussed. Elemental mapping showed no secondary phase in Tb2.45 Hf2 O7.68 ceramics. Verdet constant of the Tb2.45 Hf2 O7.68 ceramics at 633 nm is -165.6 radT −1 m −1, which is 23.6% higher than that of commercial Tb3 Ga5 O12 crystal (-134 radT −1 m −1 ) and 8.4% higher than that of Tb2 Hf2 O7 (-152.8 radT −1 m −1 ). Tb2.45 Hf2 O7.68 ceramics with high Verdet constant are promising to be used in compact Faraday rotators. Graphical abstract: Image, graphical abstract